Quantitative Evaluation of Internal Pavement Distresses Based on 3D Ground Penetrating Radar - Yong Liu; Zhiwen Zhang; Yang Yuan; Yunsheng Zhu; Kaifeng Wang (The Baltic Journal of Road and Bridge Engineering)
Asphalt pavement will inevitably produce internal distresses during service, which increases the risk of deterioration of pavement structural performance. Although three- dimensional ground penetrating radar (3D GPR) with a multi-channel antenna array can detect the internal structural condition of asphalt pavement non-destructively and quickly, there is currently a lack of effective evaluation index and standard. In this paper, 3D GPR was used to investigate four typical internal distresses of existing asphalt pavement in Guangzhou- Shaoguan Expressway, including cracks, loose, cavities, and poor interlayer bonding. In particular, GprMax software was used to establish the quantitative relationship between base crack width and radar images. Based on the radar image characteristics of different internal distresses, the distresses at the asphalt layer, base, and subbase were identified and statistically analysed. Pavement internal condition index (PICI) was proposed to quantitatively assess the internal distress condition of asphalt pavement. The results show that the PICI based on 3D GPR is reliable for evaluating the internal distress condition of pavement structure, and can be used as an important supplementary part of pavement structural integrity evaluation. The evaluation results can provide a reference for asphalt pavement maintenance decision.